Meta-Analysis of Discovery Learning Interventions in Higher Eduaction - Fahmi Qodrul Asphar; Asmawati Asmawati; Dawi Yanti; Sukini Sukini; Mohammad Edy Nurtamam; Hadi Widodo; Tomi Apra Santosa (Edumaspul: Jurnal Pendidikan, 2024)
Discovery learning is an active, student-centered teaching method, where students are encouraged to independently explore and build their own understanding of a topic. This model can improve student learning at various levels of Education including higher education. However, there is no comprehensive meta-analysis of the effect size of research models in higher education. This study aims to conduct a meta-analysis of discovery learning interventions in higher education. Data sources come from 13 national and international journals published in 2022-2024. The source data was obtained through the scientific journal database google scholar, ScienceDirect, Wiley and ERIC. The inclusion criteria in this meta-analysis are that the research must be an experimental method; research comes from SINTA or Scopus indexed journals; Research must be relevant to the discovery learning model in higher education; Journals must be open access and have complete data to calculate the effect size. The results of this study concluded that the Discovery learning model had a significant impact applied to universities with an effect size value of 1,062; p < 0.001) with very high effect size criteria. The findings of this study support the use of discovery learning interventions in higher education.